Complexity of Barriers to Biogas Digester Dissemination in Indonesia - Ibnu Budiman (Purnomo Yusgiantoro Center, 2021)
In the global south, the use of firewood and LPG as dominant energy sources for cooking contributes to socio-ecological issues. Alternatively, biogas is considered a cleaner energy source generated from organic waste. However, in Indonesia, until 2018, only less than 2 percent of households utilized biogas for cooking fuel. This research aims to explore the landscape of biogas governance in Indonesia, its fragmentation and its relation with biodigester dissemination. This study found that there is fragmentation within small-medium scale national biogas programs in Indonesia. Seven national government biogas programs have similar governance arrangements and characteristics; scattered in different departments within the ministry, using the grant approach with two main vendors, often overlapping with local government programs and not providing proper monitoring and evaluation mechanism, as well as proper training for users. Meanwhile, the biogas program by a non-government organization utilizes a semi-commercial approach; collaborating with multiple stakeholders (governments, local construction partner organizations, cooperatives and private sectors-companies and banks); and has standardized training and after-sale services. Within those biogas programs, there are multiple barriers along the supply chain process of biodigester dissemination. These barriers relate to the governance aspect of biogas programs. Fragmented governance affected the capability of each program to tackle barriers in biogas digester dissemination.